Analysis of Defense Scheme in OverLoad Shedding on 70kV Using DIgSILENT 15.1 for Enhancing the Reliability - Devyanti, Elleina Kartika; Kentjie, Muhammad Zulham; Azzahra, Septianisa; Okvasari, Rudina (Journal of Sustainable Innovation Engineering, 2025)
This research investigates the reliability of Kediri Subsystem 3,4, focusing on the impact of a Manisrejo-Nganjuk Transmission Line trip on Manisrejo-Caruban Transmission Line under normal and N-1 contingency conditions. Using Digsilent 15.1, load simulations were conducted revealing that under normal conditions, Manisrejo-Caruban Transmission Line operates at 88.92% capacity. A trip on Manisrejo-Nganjuk line could potentially overload Manisrejo-Caruban line, failing N-1 contingency requirements. To address this, Overload Shedding (OLS) was implemented on the Manisrejo-Caruban Transmission Line. Simulation results post-OLS implementation showed a reduction in line load to 64.99%, necessitating an OLS setting addition of 435.6 A. A two-stage OLS strategy was adopted: the first stage targeted OLS release at Nganjuk Substation Transformer 1, followed by the second stage at Caruban Substation Transformer 1. This effectively reduced the Manisrejo-Caruban Transmission Line load to 58.1% of its capacity. Economically, PT. PLN (Persero) benefited significantly from this implementation, saving Rp. 42,170,793 in costs. These findings underscore the efficacy of OLS strategies in enhancing system reliability and mitigating overloads, thereby optimizing operational efficiencies and cost savings for power utilities.